Gettysburg--The First Day - Pfanz, Harry W. (Harry Willcox), 1921-2015 (Book collections on Project MUSE., 2001)
"Though a great deal has been written about the battle of Gettysburg, much of it has focused on the events of the second and third days. With this book, the first day's fighting finally receives its due. Harry Pfanz, presents a definitive account of the events of July 1, 1863"--Jacket